2014
DOI: 10.1055/s-0034-1390795
|View full text |Cite
|
Sign up to set email alerts
|

Water exchange versus carbon dioxide insufflation in unsedated colonoscopy: a multicenter randomized controlled trial

Abstract: There was no significant reduction in moderate or severe pain in a comparison of water exchange with CO2 insufflation. The secondary outcome of no pain was significantly more frequent in the water exchange group. Clinical trials registry number: NCT01633333.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 24 publications
3
52
0
Order By: Relevance
“…Recent publications have suggested that WE produced the lowest insertion pain. 1,2,4,5,[9][10][11] Our current data (Tables 1 and 2) confirm these observations. The WE technique reproducibly achieved the lowest insertion pain not only in men, but also in women (Table 3), who usually report more pain during colonoscopy.…”
Section: Q16supporting
confidence: 84%
See 1 more Smart Citation
“…Recent publications have suggested that WE produced the lowest insertion pain. 1,2,4,5,[9][10][11] Our current data (Tables 1 and 2) confirm these observations. The WE technique reproducibly achieved the lowest insertion pain not only in men, but also in women (Table 3), who usually report more pain during colonoscopy.…”
Section: Q16supporting
confidence: 84%
“…[4][5][6] The description of water-aided methods varies in previously published studies. How these are used in actual practice is unknown.…”
Section: Q16mentioning
confidence: 99%
“…47 A recent, randomized, single-blind study compared CO 2 insufflation (n Z 226) with water infusion (n Z 226) during colonoscope insertion, with all patients undergoing insufflation with CO 2 during colonoscope withdrawal. 45 Colonoscopy was initiated without sedation, but "on demand" sedation was administered as necessary to patients. The study indicated no difference in the eventual need for sedation medications between both groups.…”
Section: Clinical Experiencementioning
confidence: 99%
“…The successful intubation rate without sedation with traditional air insufflation (AI) varied widely from 34% to 94%. 5,10,11 The on-demand sedation option has certain advantages over full sedation. The completion rates without sedation were generally higher with WE, ranging from 78% to 94%.…”
Section: Introductionmentioning
confidence: 99%
“…The completion rates without sedation were generally higher with WE, ranging from 78% to 94%. 5,10,11 The on-demand sedation option has certain advantages over full sedation. Use of sedation is associated with a small but real risk of cardiopulmonary complications.…”
Section: Introductionmentioning
confidence: 99%